PENDAMPINGAN AKTIVITAS BELAJAR MENGAJAR SANTRI DI MASA PANDEMI COVID-19 DI PONDOK PESANTREN BABURROHMAT DESA RANCAPANGGUNG KECAMATAN CILILIN KABUPATEN BANDUNG BARAT - Awan Gunawan (LPPM STAI Darul Falah, 2022)
The covid pandemic caused teaching and learning activities in Rancapnggung Village to be less effective. Students' declining learning interests have an impact on the quality of education. Not not gone unnoticed, Pondok Pesantren Institution was affected so that the interest in learning santri was lacking. Therefore, this KKN activity is carried out in order to help increase the spirit of learning, especially Baburrohmat santri. To improve this, the need for assistance and supervision in the teaching and learning process in the pandemic period, collaboration between teachers and parents is also carried out in order to get intensive supervision in learning. Education is basically an effort to improve the ability to become a human being who has character and can live independently. This is the main purpose of the implementation of KKN in order to realize the character of students who are noble. Thus, if the noble characters are embedded in santri and learners, it will automatically be reflected in the behavior of daily life.